Some Curvature Conditions on a Para-Sasakian Manifold with Canonical Paracontact Connection - Bilal Eftal Acet; Erol Kılıç; Selcen Yüksel Perktaş (International Journal of Mathematics and Mathematical Sciences)
We study canonical paracontact connection on a para-Sasakian manifold. We prove that a Ricci-flat para-Sasakian manifold with respect to canonical paracontact connection is an η-Einstein manifold. We also investigate some properties of curvature tensor, conformal curvature tensor, W2-curvature tensor, concircular curvature tensor, projective curvature tensor, and pseudo-projective curvature tensor with respect to canonical paracontact connection on a para-Sasakian manifold. It is shown that a concircularly flat para-Sasakian manifold with respect to canonical paracontact connection is of constant scalar curvature. We give some characterizations for pseudo-projectively flat para-Sasakian manifolds.